2020
DOI: 10.3390/ijerph17218137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorder Risk and Body Image Dissatisfaction among ROTC Cadets

Abstract: Injury risk is multifactorial including non-modifiable and modifiable factors such as nutrition and mental health. The purpose of this study was to estimate eating disorder risk and body image (BI) dissatisfaction among Reserve Officers Training Corps (ROTC) cadets. A total of 102 (male: n = 75, female: n = 27; age: 20 ± 2 years) ROTC cadets self-reported height, current and ideal weight, and completed the Eating Attitudes Test-26 (EAT-26) and self-perceived BI current and perceived sex-specific figural stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…These findings are like previously reported ED risk ranging from 25–42% within aesthetic athletes [ 13 , 15 , 16 , 30 ]. Additionally, our results are comparable to ED prevalence rates previously reported in other non-aesthetic sports and physically active populations: 8% of soccer athletes [ 31 ], 11% of elite female athletes from various sports [ 32 ], 29% of auxiliary units [ 14 ], 32% of ROTC cadets [ 33 ], and 42% of equestrian riders [ 34 ]. Specifically, within the college cheerleading population, ED risk prevalence was previously reported at 33.1%, consistent with our findings [ 3 ].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are like previously reported ED risk ranging from 25–42% within aesthetic athletes [ 13 , 15 , 16 , 30 ]. Additionally, our results are comparable to ED prevalence rates previously reported in other non-aesthetic sports and physically active populations: 8% of soccer athletes [ 31 ], 11% of elite female athletes from various sports [ 32 ], 29% of auxiliary units [ 14 ], 32% of ROTC cadets [ 33 ], and 42% of equestrian riders [ 34 ]. Specifically, within the college cheerleading population, ED risk prevalence was previously reported at 33.1%, consistent with our findings [ 3 ].…”
Section: Discussionsupporting
confidence: 89%
“…ROTC cadets are also a unique subset of the college student population, having to navigate the college environment while also maintaining U.S. Army fitness and body composition standards. Due to multiple obligations, such as regular physical training, academic assignments, the introduction to military procedures, and the expected lifestyle changes that occur in college, cadets are susceptible to poor eating habits, poor body image, and disordered eating [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cadets had a significantly higher drive for thinness and body dissatisfaction6 ; a second study by Lauder et al of 423 female soldiers found that 8% of women were diagnosed with an eating disorder 10. Smith et al reported a multitude of pathological behaviours in Reserve Officers’ Training Corps cadets such as binge eating; the use of laxatives, diuretics or diet pills; and excessive exercise 29. Campagna and Bowsher 11 reported prevalence rates of BDD (13% in men, 22% in women, 18% in soldiers, 12% in sailors, 13% in airmen) and prevalence rates of MD (13% in men, 4% in women).…”
Section: Resultsmentioning
confidence: 99%
“…Women expressed more dissatisfaction with their appearance and lower self-esteem compared with men5 which might explain the higher prevalence of BDD found in women 11. Apart from BDD and MD and their symptoms, eating disorders, eating disorder symptoms and disordered eating were also reported to be highly prevalent in military personnel, particularly in women 3 8–11 29 30…”
Section: Discussionmentioning
confidence: 98%